Platelet Depletion and Severity of Streptococcal Endocarditis - Lawrence Dall; Todd Miller; Betty Herndon; Ireneo Diez; Michelle Dew (Canadian Journal of Infectious Diseases)
OBJECTIVE: To evaluate the importance of thrombocytopenia in streptococcal endocarditis using an animal model.